Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300413
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Props in VR Climbing Environments

Abstract: Dealing with fear of falling is a challenge in sport climbing. Virtual reality (VR) research suggests that using physical and reality-based interaction increases the presence in VR. In this paper, we present a study that investigates the influence of physical props on presence, stress and anxiety in a VR climbing environment involving whole body movement. To help climbers overcoming fear of falling, we compared three different conditions: Climbing in reality at 10 m height, physical climbing in VR (with props … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Similarly, Bystrom et al contend, that the relationship between presence and performance is task-specific and performance only increases with greater presence if the latter is relevant for the task [13]. However, a substantial body of research shows evidence that the immersive characteristics of a VE can promote task performance [62,71,94], learning outcomes [1,16,17,57] and therapy effects [15,23,41,31].…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, Bystrom et al contend, that the relationship between presence and performance is task-specific and performance only increases with greater presence if the latter is relevant for the task [13]. However, a substantial body of research shows evidence that the immersive characteristics of a VE can promote task performance [62,71,94], learning outcomes [1,16,17,57] and therapy effects [15,23,41,31].…”
Section: Related Workmentioning
confidence: 99%
“…A number of studies have shown that haptic feedback fosters embodied interaction, presence and immersion in virtual environments (e.g. [2,5,14,34,35]). Generally, this feedback is provided either by active or passive haptics.…”
Section: Haptics In Virtual Environmentsmentioning
confidence: 99%
“…The use of haptic thermal feedback as an interaction mechanism within VR technologies is an emerging interest to increase the engagement and feeling of immersion for the user [4,10,12,13,19,22]. One aspect that was challenging was to define the number of heat elements to use and their placement on the user.…”
Section: Discussionmentioning
confidence: 99%